(untitled) (Indian Journal of Animal Production and Management, 2024)
A total of 1007 local donkeys were selected for the study of phenotypic and reproductive characters of local donkeys from different districts of the Marathwada region in Maharashtra state. Statistically non-significant differences were found in most of the phenotypic parameters. Four different body coat colour patterns i.e., grey, brown, white, and dark red brown were observed with percentage as 48.46, 21.54, 25.12 and 4.86%, respectively. Most of donkeys (96.02 %) were black muzzled with convex forehead (93.24%), white marking above muzzle (66.53%), white marking above eyes (67.72%), white marking posterior to the mandible (70.30%), dark brown lining around extremity of ear pinna (88.97 %), long white hairs at inner side of ear pinna (100%) and bearing dark strip starting from poll to switch of tail and forming cross with another dark strip at shoulder (73.48%). The mean age at puberty, age at first service, age at first oestrus, oestrus cycle duration, oestrus duration, age at first covering, age at first conception, no. of services/conception, age at first foaling, service period, foaling interval, gestation period, lifetime no. of foaling of adult female local donkeys in Marathwada region were 2.70±0.02 years, 2.79±0.02 years, 2.77±0.03 years, 6.86±0.084 days, 23.80±0.55 days, 2.96±0.01 years, 5.9±0.07 years, 1.82±0.06, 4.44± 0.01 years., 1.14±0.01 years, 2.25±0.01 years, 340.8±0.27 days and 5.98±0.07, respectively.